The current status of environmental requirements for deep seabed mining issued by the International Seabed Authority. (April 2020) - Bräger, Stefan; Romero Rodriguez, Gabriela Q.; Mulsow, Sandor
Abstract: Up to September 2018, the International Seabed Authority has issued a total of 100 mandatory requirements (published between 2011 and 2015) as guidance for potential future miners when collecting data for their environmental baseline studies during the exploration phase. An in-depth analysis of all current requirements highlights twelve themes covered by multiple requirements: methodology for seabed sampling, methodology for water column sampling, statistical evidence, spatio-temporal considerations, toxicology, modelling needs, genetic studies, species-specificity, documentation and archival storage, impact-related studies, area-based management tools, and comparison and assessment. Within each theme, the relevant requirements are compared with each other to allow a comprehensive assessment of the research effort needed to satisfy all of the 100 requirements. Highlights: 100 regulations define environmental baseline studies by each contractor under ISA exploration contract. We present 12 cross-cutting themes for a regulatory roadmap set out by UNCLOS and substantiated by LTC guidance. Each theme calls for a critical review of the baseline work carried out during 15 years of exploration. A poor baseline may cause a suboptimal EIA providing weak support for a mining permit.